Emerging Trends and Hot Spots in Hepatic Glycolipid Metabolism Research From 2002 to 2021: A Bibliometric Analysis - Zhou, Yanyu; Lin, Xiaoqi; Yin, Suqing; Zhu, Ling; Yang, Yuting; Li, Yixuan; Wang, Baoshan; Jiao, Yingfu; Yu, Weifeng; Gao, Po; Yang, Liqun (Frontiers in Nutrition, 2022)
Glycolipid metabolic diseases including type 2 diabetes, non-alcoholic fatty liver disease, obesity, hypertension, dyslipidaemia and atherosclerosis, which have become a major public health concern worldwide, are mainly triggered by hepatic glycolipid metabolism disorder. Bibliometric analysis provides a comprehensive review of developments in hepatic glycolipid metabolism research and changes in research hotspots over the past 20 years. The articles regarding hepatic glycolipid metabolism from 2002 to 2021 were identified from the Science Citation Index-Expanded of Web of Science Core Collection. Acquired data were then processed by the CiteSpace software and the Online Analysis Platform of Literature Metrology to analyze trends and predict hot spots in this field. A total of 4856 articles regarding hepatic glycolipid metabolism published from 2002 to 2021 were selected. The leading country was China. The Chinese Academy of Sciences was the most productive institution. Co-citation cluster labels revealed characteristics of ten main clusters: non-alcoholic fatty liver disease, gut microbiota, adiponectin, fructose, fgf21, fatty acid, liver x receptor, nr4a, obese mice and bile acids. Keyword bursts analysis indicated that management, non-alcoholic fatty liver disease and modulation were the newly emerging research hotspots. We described the overall structure of scientific research on hepatic glycolipid metabolism and presented systematic information to other researchers. The current focus on NAFLD and gut microbiota is critical for further study and will help explore effective therapeutic strategy for aberrant glycolipid metabolism in liver.